Metode Analisis Konjoin Terhadap Preferensi Konsumen Minyak Goreng Kemasan - Frasetyo, Ahmad Al; Hernosa, Siswa Panjang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Cooking oil that is measured in liters and packaged in bottles, refills, and derigens is called packaged cooking oil. Branded packaged cooking oil, which has better quality than bulk cooking oil, can be purchased in stores through product labels, packaging, and brands. The purpose ofthe research is to find out the characteristics of consumers, attributes and levels and the order of attributes of packaged cooking oil. Data analysis methods validity test, reliability test and conjoin analysis. The results of the study showed that: The validity test of brand attributes, packaging, price, size, clarity and color was declared valid seen through a sig<0.05 value and in the reliability test all statement items were declared moderate reliability seen from Cronbach's Alpha 0.50–0.70. 1. Female respondents are the most buyers of packaged cooking oil. A total of 36 people were in the age group of 33-41. Respondents with 3-4 family members were the largest, namely 51 people. The most consumers are respondents with junior high school education, which is 34 people. The respondents to packaged cooking oil with the largest type of work are 65 consumers of housewives. The respondents of packaged cooking oil with the most income were IDR 2,500,000 – IDR 4,000,000 totaling 36 people. 2. The attributes of packaged cooking oil that are a consumer benchmark seen from the utility value are the size of 1 l, clear clarity, price > IDR 31,000, golden yellow color, bimoli brand, bottle packaging. 3. The order of attributes of packaged cooking oil according to the interests of packaged cooking oil consumers is size, clarity, price, color, brand, and packaging. It was obtained that size is the most calculated attribute of consumers in buying packaged cooking oil and is the most calculated preference of traders in the supply of packaged cooking oil.